Urban air pollution and chronic respiratory diseases in adults: insights from a cross-sectional study - Alyami, Mohammed M.; Balharith, Fahad H.; Ravi, Sunil Kumar; Reddy, Ravi Shankar (Frontiers in Public Health, 2025)
ObjectivesAir pollution poses a substantial public health risk, especially in urban environments characterized by elevated levels of pollutants such as fine particulate matter (PM2.5) and nitrogen dioxide (NO2). These pollutants negatively impact respiratory health, contributing to chronic respiratory conditions and reduced lung function. This study investigated the association between air pollution exposure and respiratory health outcomes, including the prevalence of chronic respiratory conditions and pulmonary function, in an urban population. Additionally, the study sought to identify demographic subgroups that are unprotected from the ill effects of air pollution.MethodsA cross-sectional study included a total of 1,300 adult participants recruited from outpatient pulmonary and general medicine clinics. Air pollution exposure was assessed based on residential proximity to major traffic routes and ambient levels of PM2.5 and NO2 obtained from the Riyadh air quality monitoring network. Lung function was measured using spirometry, and data on chronic respiratory conditions were collected through self-reports and medical record reviews. Multivariable logistic regression and linear regression models were used to analyze the association between air pollution exposure and respiratory outcomes, adjusting for confounders such as age, gender, smoking Status, socioeconomic Status, physical activity, and occupational exposures.ResultsHigher air pollution level exposures were significantly associated with an increased prevalence of chronic respiratory conditions (adjusted OR for high exposure: 2.45, 95% CI: 1.70–3.55, p < 0.001) and a reduction in lung function, as indicated by declines in FEV1 and FVC (adjusted FEV1 coefficient for high exposure: -0.45, 95% CI: −0.58 to −0.32, p < 0.001). Subgroup analyses revealed that older adults, males, and current smokers were particularly susceptible to the adverse effects of air pollution. Sensitivity analyses confirmed the robustness of these findings across different analytical scenarios.ConclusionThe study demonstrated a clear and significant association between higher air pollution level exposures and an increased risk of chronic respiratory conditions and reduced lung function. These findings highlight the need for specific interventions to decrease air pollution exposure, particularly in vulnerable urban populations, to mitigate the burden of respiratory diseases.